Sex hormones and reproductive factors with cardiac arrhythmia and ECG indices: a mendelian randomization study - Xishu Wang; Zhaoyang Wei; Zheng Zuo; Ying Sun; Xiaoxue Guo; Yi Tong; Guanghui Liu; Dongyang Xu; Zhiguo Zhang (BMC Cardiovascular Disorders)
Abstract Background Sex is a determinant of the incidence and etiology of arrhythmia. Observational and basic studies suggest that sex hormones are essential in this process; however, the relationship between sex hormones and arrhythmia remains unclear. Mendelian randomization (MR) was used to investigate the causal relationships between sex hormone levels, arrhythmia, and electrocardiographic (ECG) indices. Methods Large genome-wide association studies (GWAS) data on sex hormones, stratified by sex, from the UK biobank consortium, were used as exposure data, and data on atrial fibrillation (AF), atrioventricular block, sick sinus syndrome, paroxysmal tachycardia, and ECG indices were obtained from the FinnGen consortium and summarized large GWAS data. Inverse variance weighting or wald odds was used as the primary analytical method, and weighted medians and MR-Egger regression were used for complementary analyses. The results of the MR of sex hormones and AF from different sources were analyzed using a meta-analysis. Summary-data-based MR analysis was utilized to explore the relationship between sex-hormone related drugs and arrhythmia. Results In men, genetically predicted higher estradiol concentrations were associated with a lower risk of AF (odds ratio: 0.908 [0.852–0.967]; p = 0.0029], whereas genetically predicted higher concentrations of total testosterone were associated with lower heart rate variability. Sex hormones showed no association with atrioventricular block, sick sinus syndrome, paroxysmal tachycardia, resting heart rate, P wave duration, P wave terminal force in lead V1 [PTFV1], PR interval, QRS duration, QTc [QT interval corrected by heart rate], ST duration, spatial [spQRSTa] and frontal [fQRSTa] QRS-T angles in males. In females, there was no significant evidence that sex hormones are associated with arrhythmias or ECG indices. Conclusion In this study, we identified a potential causal relationship between estradiol and the risk of AF in males. However, there was no significant association between sex hormones and either arrhythmias or ECG indices in females. These results suggested that sex hormones may play a limited role in cardiac arrhythmias, which requires further verification.